Ta'aqquli Behavior and Its Effect on Customer Satisfaction and Loyalty of Islamic Banks: A Study on Muslim Student Customers - Darma Taujiharrahman; Irene Rini Demi Pangestuti (Jurnal Akuntansi dan Pajak, 2023)
Indonesian Islamic banks as determined by the ta'aqqul behavior approach to consumption. In order to build a marketing framework model that Islamic banks can employ, this study combines two consumer behavior-based marketing theories, namely the expectation disconfirmation theory and the Islamic consumer behavior theory. Service quality and sharia compliance are employed as proxies for the expectation disconfirmation theory and Muslim consumer behavior, respectively. Data for data analysis were gathered through a survey with 100 responses. The analytical technique employs SEM with the PLS approach to analyze the measurement and structural model. According to the study's findings, Muslim customer loyalty is immediately and significantly positively impacted by service quality and customer happiness. The indirect effect of sharia compliance through satisfaction is hence positive but not significant, but the indirect effect of service quality through satisfaction is positive and substantial. This study offers helpful details that Islamic banking can employ to enhance its marketing effectiveness.